Pengaruh Aplikasi E – Manajemen Penyidikan dan Budaya Organisasi terhadap Kinerja Penyidik dalam Penanganan Perkara Pidana di Polres Teluk Bintuni - Mas Juli; Yelly Febrina Zani; widya spalanzani (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Police as an Institution that has many divisions and staff who need an information system in order to help speed up obtaining information needs. The government’s efforts in launching the e_ Investigations Management application to Support Polri’s services in the field of investigation so that it is Proffesional, Modern and Reliable ( Promoter ). In the investigation, the criminal Investigation unit of the Bintuni Bay Police has used the E_ Investigation management application which aims to enable the public to easily access all information. This study aims to determine whether or not there is an influence of the application of e_ Investigation management and organizational culture on the performance of investigators in handling criminal cases at the Teluk Bintuni Police station. This research is a quantitative research. The samle in this studt amounted to 76 people with a sampling technique using simple random sampling. Data collection techniques were carried out through questionnaires and literature study. Hypothesis testing using classical assumption test and simple regression analysis using IBM SPSS Ver 21.0 application to determine the contribution of the independent variable to the dependent variable at the 95 % trend level (α = 0.05). The results are : 1 ) there is not Positive and significant effect between the application of e_ Investigation management on the performance of investigators in handling criminal cases at the Bintuni Bay Police. 2 ) there is a positive and significant influence between organizational culture on the performance of investigators in handling criminal cases at the Teluk Bintuni Police station. And 3 ) there is a significant effect between the application of e_ Investigation management and organizational culture together on the performance of investogators in handling criminal cases at the Teluk Bintuni Police Station.